N-Cryptographic Multilevel Algorithm for Effective Information Security - Adebayo, Olawale S; Olalere, Morufu; Mishra, Amit; Ugwu, Joel N.; Mabayoje, M. A. (Discoveries in Agriculture and Food Sciences, 2014)
Security of information cannot be perfectly realized as both it and its counter technology continue to evolve. In the same vein, using a single cryptographic cipher to realize information secrecy is not enough as it can be broken over time, thus revealing the information in plaintext. Most of the existing cryptographic ciphers possess a minimal level of weakness, which is exploitable over time, but when this algorithmic transformation is used in multiple times, the number of trials, effort, and time required to exploit it become greater. This paper proposes a multilevel algorithm for realizing the security of information using a multiple-cryptographic ciphers process. It presents the possibility of combining n-cryptographic ciphers in a single implementation within the system, permitting n-cryptographic transformation to take place during the encryption and decryption processes.